PENDEKATAN PARTISIPATIF DALAM PENGELOLAAN DANA DESA DI WILAYAH KECAMATAN BAMBAIRA KABUPATEN PASANGKAYU - Aswin, Budi (Katalogis, 2020)
This research aims to find out how the participative Approach of village fund management in Bambaira village district. The research used a descriptive qualitative type. The data used were primary and secondary data. The data were gathered using observation, interview and documentation. The data analysis used was from Miles and Huberman model consistingof data reduction, data display, and drawing conclusion. The theory used Ericson theory coverting three aspects, namely: participastion in planning, participation in implementation, and participation in managing village fund in Bambaira district find many problems if it is seen from the stage of planning, that very dominant or more active during village fund management discussion is the village officials, the members of village consultative board and public figures considered have influential. Meanwhile most of the villagers do not really active in playing role on the planning stage because they did not get the invitation to the discussion, so the making decision time does not represent the aspiration of the villagers in general. Furtheremore, the villagers have lack awarenessof the development of the village. This indication is seen on the policy implementation of the village fund management, begin from the planning process to the final implementation which almost done by the village government only. Village communities who should act as a determinant of village development tend to be only spectators in every development in the village. In addition, there is still a low awareness of the village community to maintain the existing infrastructure, due to a lack of public understanding of the importance of maintaining development infrastructure/program. Based on the description above, it can be concluded that community participation in village fund management is still very low and far from what was expected.